A spatially explicit data-driven approach to calculating commodity-specific shipping emissions per vessel. (20th December 2018) - Schim van der Loeff, Wendela; Godar, Javier; Prakash, Vishnu
Abstract: Oceangoing ships carry approximately 80% of the world's traded goods by volume, which translates into more than 10 billion tonnes in shipped traded volumes per year (UNCTAD, 2017 ). Despite its importance, the maritime shipping sector has been traditionally overlooked in climate mitigation discussions, since this sector was largely neglected in the 1997 Kyoto Protocol. Key barriers for successful implementation of CO2 abatement measures in the sector include the lack of reliable emissions data and the inherent difficulty of attributing responsibility for international shipping emissions to the involved countries, companies and commodities, as well as the threat to global trade interests. We argue that the data paucity on maritime emissions from international trade can be addressed by linking and integrating a large wealth of data, previously used in isolation. By linking per vessel cargo composition data, individual vessel journeys from the Automatic Identification System and a bottom-up methodology to estimate emissions, using vessel specifications and details on their movements and operations, this paper describes and demonstrates this new approach for the case of Brazil's shipping manifests in 2014. We find that the maritime transportation associated with these trades is responsible for 25.99 million tonnes of CO2, an addition of 5% to Brazil's total CO2 emissions of 2014 (reported by the World Bank, currently excluding international shipping and aviation). We discuss the contribution of all traded commodities, as well as the role of the first destination ports and countries. The voyage- and commodity-specificity of this method allows us to showcase those commodities and trading routes which contribute the most towards this emissions account, in relation to those that are most valuable to Brazil's economy. We go on to discuss the implications of scaling up this methodology for global greenhouse gas abatement efforts and demand-side footprint calculations, as well as to improve accountability mechanisms for the maritime sector as a whole.